2000
DOI: 10.1080/000164700317413085
|View full text |Cite
|
Sign up to set email alerts
|

No effect of low-dose aspirin for the prevention of heterotopic bone formation after total hip replacement: A randomized trial of 2,649 patients

Abstract: -2,649 patients scheduled for elective total hip replacement were recruited to the Heterotopic Bone Formation Sub-study of the Pulmonary Embolism Prevention Trial. Heterotopic bone formation was determined by radiographic examination and associated late postoperative outcomes were assessed by telephone interview. Heterotopic bone formation was observed in 627 (31%) of 2,048 radiographic examinations. There was no detectable effect of low-dose aspirin on the risks of heterotopic bone formation (RR 0.98; 95%CI 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 9 publications
0
33
1
Order By: Relevance
“…2). The findings of the plots restricted to HBF grades 0−2 were also inconsistent, 37 although the one large study 39 showed a trend toward worse pain with increasing grades of HBF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). The findings of the plots restricted to HBF grades 0−2 were also inconsistent, 37 although the one large study 39 showed a trend toward worse pain with increasing grades of HBF.…”
Section: Resultsmentioning
confidence: 99%
“…Data on the association of HBF with late postoperative function were reported by 16 studies (5918 participants) 7,11,17−22,30−32,38−42 . The principal component of function measured by most studies was walking ability.…”
Section: Resultsmentioning
confidence: 99%
“…(We contacted the authors and found out that the dosage, when known, was 325 mg daily [Jaimo Ahn, personal communication, February 8, 2012].) Another study of humans demonstrated no significant effect of 162 mg of aspirin daily on heterotopic ossification following total hip arthroplasty 18 . However, the authors did not assess bone healing or ingrowth.…”
mentioning
confidence: 99%
“…A large prospective study of 2649 patients found that aspirin was ineffective in preventing HO formation [10]. More recently, a retrospective study comparing first-stage bilateral total hip arthroplasty patients treated with aspirin versus coumadin demonstrated a significant reduction in the prevalence and severity of HO with aspirin [11].…”
Section: Aspirinmentioning
confidence: 99%